2016
DOI: 10.1515/jcim-2014-0079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6 months intense Yoga practice on lipid profile, thyroxine medication and serum TSH level in women suffering from hypothyroidism: A pilot study

Abstract: 6 months practice of yoga may help in improving cholesterol level, serum TSH, may also help in reducing the thyroxine requirement in female patients suffering from hypothyroidism. However, further randomized controlled studies need to be conducted to confirm the present finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…In sixteen individuals (nine female) with elevated depression and anxiety symptoms, two months of mindfulness meditation practised at least three times a week similarly did not influence TSH, T3 and T4 levels, though this study did not assess males and females separately [31]. In a pilot study of 22 women with hypothyroidism, however, six months of yoga practice four times a week, including cyclic meditation, resulted in a non-significant reduction in TSH, cholesterol, triglycerides, low density lipoprotein and high-density lipoprotein levels [58]. These results indicate that meditation may improve thyroid function in women with thyroid dysfunction more effectively than in women with normal thyroid function, or that interventions of longer duration are required in order to detect benefits following meditation interventions.…”
Section: Meditation Influences the Hypothalamic-pituitary-thyroid (Hpmentioning
confidence: 66%
“…In sixteen individuals (nine female) with elevated depression and anxiety symptoms, two months of mindfulness meditation practised at least three times a week similarly did not influence TSH, T3 and T4 levels, though this study did not assess males and females separately [31]. In a pilot study of 22 women with hypothyroidism, however, six months of yoga practice four times a week, including cyclic meditation, resulted in a non-significant reduction in TSH, cholesterol, triglycerides, low density lipoprotein and high-density lipoprotein levels [58]. These results indicate that meditation may improve thyroid function in women with thyroid dysfunction more effectively than in women with normal thyroid function, or that interventions of longer duration are required in order to detect benefits following meditation interventions.…”
Section: Meditation Influences the Hypothalamic-pituitary-thyroid (Hpmentioning
confidence: 66%
“…A previous study showed significant reduction in total cholesterol, LDL and triglycerides, and significant improvement in HDL cholesterol following six months of intense yoga in women suffering from hypothyroidism. 20 Another study on 20 hypothyroidism women, on 1 month of yoga practice showed significant improvement in the quality of life, and study by Swami et al on 6 months of pranayama practice improved forced expiratory volume in lung function test of women with hypothyroidism. 21 Previous studies have shown beneficial effects of naturopathy treatments in relation to body weight, lipid profile and blood pressure in obese individuals.…”
Section: Discussionmentioning
confidence: 95%
“…The intervention has been systematically developed through reviewing earlier studies on effects of yoga practises on hypothyroidism and its symptoms. [23][24][25][26][27] The intervention is delivered by a qualified and experienced yoga instructor, qualified with formal training provided on the intervention protocol. Yoga sessions are run as per convenience of the participants.…”
Section: Intervention (Yoga)mentioning
confidence: 99%
“…17 An RCT conducted by Nagendra et al reported reduction in TSH level, total cholesterol, low-density lipoprotein (LDL), triglycerides along with significant improvement in high-density lipoprotein (HDL) in hypothyroid patients. 18 Another study conducted on 150 obese and hypothyroid female patients reported remarkable benefits from low-calorie diet along with yoga. 19 Another RCT recently conducted to assess the effect of yoga on overt hypothyroid patients carried out in Delhi also reported beneficial effects on both biochemical parameters (TSH, T3, T4) as well as on psychological parameters (WHO-QOl, PSQI, BDI-II) following 6 months of yoga intervention.…”
mentioning
confidence: 99%